Effect of weathering on environmental behavior of microplastics: Properties, sorption and potential risks - Liu, Peng; Zhan, Xin; Wu, Xiaowei; Li, Jinli; Wang, Hanyu; Gao, Shixiang (Chemosphere (Oxford), 2020)
Microplastic (MP) pollution is a raising global concern in recent years due to its wide distribution. Additionally, most of the MPs have undergone extensive weathering in the environment, and weathered MPs may exhibit different physicochemical properties from pristine ones. The review reveals the change in physicochemical properties (e.g. size, color, crystallinity, mechanical property and oxygen-containing groups) and the release of additives and MP-derived intermediates (i.e. oligomers and oxygenated compounds) during weathering processes. Weathering further affects the sorption behavior of MPs for environmental pollutants because of the changed crystallinity, specific surface area and oxygen functional groups. The interaction mechanisms of pristine and weathered MPs with pollutants are summarized, and how weathering processes affect sorption behavior is critically revealed. Because of the changed size, color and surface charges, weathered MPs might be ingested by aquatic organisms in different ways from the pristine ones. The detailed effects of weathering on the ingestion of MPs are discussed, and the potential toxicity of leachates from weathering processes is evaluated. In addition, the environmental components (e.g. natural organic matter and salinity) and biofilm correlated to the sorption behavior of MPs are reviewed. As for the knowledge gap, further studies should focus on the long-term weathering of MPs and the relationships between weathering properties and sorption capacities toward pollutants. The potential risks of weathered MPs and leachates on organisms should be explored. [Display omitted] •Weathering significantly changes the physicochemical properties of microplastics.•Surface area, oxygen groups and crystallinity critically affect sorption of pollutants.•Effects of weathering on the risks of microplastics and leachates are revealed.•NOM, salinity and biofilms involved in the environmental behavior are reviewed.